PEMASARAN DESA WISATA KALIBUNTUNG DALAM MENDUKUNG PENGEMBANGAN PARIWISATA DI KABUPATEN BANTUL - Ratnaningtyas, Yohana Ari; Widyasmoro, Agnes (Jurnal Kepariwisataan Indonesia: Jurnal Penelitian dan Pengembangan Kepariwisataan Indonesia, 2017)
The development of tourism village has not achieved its optimal result, therefore the impact on the economic, social, cultural, and environmental has not been maximized yet. Hence an effective strategy is highly needed through the awareness and empowerment of Kalibuntung society in regard of the importance of the tourism village development. The aim of this study is to determine the various potentials in the tourism village of Kalibuntung, to know how they apply the marketing strategy, the participation and the empowerment of the society, as well as the support from the government in developing the tourism in Bantul. This research was conducted using qualitative methods and descriptive analysis. Data were obtained by using several techniques namely observation, interview, and documentation. The results showed that the effective marketing is by using social media networks which is familiar among the youth. The conclusion is that the number of tourist visits is still limited in the region of Yogyakarta and surrounding areas. Hence there is more opportunity to develop it into various regions and targeting foreign tourists. The recommendation then suggested that it is necessary to increase cooperation with stakeholders such as travel agencies, hotels and the needs to involve the local community, and the support of the government for the development and marketing of this tourist village.